2021
DOI: 10.3390/su13168701
|View full text |Cite
|
Sign up to set email alerts
|

SLICE: An Innovative Photovoltaic Solution for Adaptive Envelope Prototyping and Testing in a Relevant Environment

Abstract: The development of adaptive architectural envelopes is one of the goals of researchers that aim to improve the energy performance of buildings. Traditional devices often have drawbacks linked to the complexity of the kinetic systems used, as the mechanical systems for guaranteeing proper operation are complex and expensive (e.g., hinges). Adaptive envelopes require energy for driving the mechanical components and management systems. Thus, it is useful for such adaptive elements to be self-sufficient, generatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…So, it was observed that the charging board did not have suitable dimensions, and as a consequence, it was not possible good store the energy produced by the PV cells. For this reason, the development of this research foresees the redesign of the recharging system and also the addition of an MPPT (Maximum Power Point Tracker) controller, which will allow the photovoltaic cells to operate at their point of maximum power [16].…”
Section: Prototypingmentioning
confidence: 99%
“…So, it was observed that the charging board did not have suitable dimensions, and as a consequence, it was not possible good store the energy produced by the PV cells. For this reason, the development of this research foresees the redesign of the recharging system and also the addition of an MPPT (Maximum Power Point Tracker) controller, which will allow the photovoltaic cells to operate at their point of maximum power [16].…”
Section: Prototypingmentioning
confidence: 99%
“…Based on the hypothesized usage scenario, the EP was equipped with three units. In order to render the module self-sufficient even on cloudy days, it must also be provided with a backup battery [6].…”
Section: Finishing Systemmentioning
confidence: 99%
“…From a holistic standpoint, sustainability in the building sector must be viewed in terms of all of a building's life stages [5], including the supply of raw materials and the production, operation, and final disposal of building components. This forward-looking vision also aimed to overcome the initial view, in which sustainability was mainly focused on energy savings [6].…”
Section: Introductionmentioning
confidence: 99%
“…Nearly Zero Energy Building (NZEB) can be one of the solutions to this problem. In fact, NZEB has very high-energy performances [3] [4]; and the very low or almost zero energy demand should be satisfied through renewable sources [5]. One of the techniques that can be used in buildings to reduce energy consumption concerns the construction of ventilated roofs and façades, whose external cladding system creates an air gap with the perimeter envelope of the building [6].…”
Section: Introductionmentioning
confidence: 99%